The Effect of Work Stress, Work Conflict, and Work Environment on Work Productivity Case Study on Project Design and Project Build at Interior Design Company in Bandung - Naszha Utami Ekaputri; Agus Riyanto (Journal of Economics, Management, Business and Accounting (JEMBA), 2022)
This study aims to find out how the influence of work stress, work conflicts and work environment on the work productivity of employees at Perusahaan Interior Design Bandung The problem that occurs is employees who cannot be avoided from stress and conflicts in their work environment so that it has an impact on their work productivity. The method used in this study is the Multiple Regresion method with a descriptive and verifiable research approach. The sampling technique used a census so that a research sample of 30 employees was obtained. Data collection techniques use interviews, observations, questionnaires and documentation. By using ibm SPSS 25.0 program software. The results of this study prove that work stress, work conflicts, work environment and work productivity in the criteria are quite good, Partially and simultaneously work stress and work conflicts have a significant negative effect on the work productivity of employees at Interior Design Company in Bandung.